18-month follow-up of randomized controlled trial of parent and child enhancement program. Issue 6 (2nd November 2018) - Leung, Cynthia; Tsang, Sandra; Chan, Lok Yan
ABSTRACT: Objective : This study aimed to evaluate the 18-month effectiveness of the Parent and Child Enhancement (PACE) program through an 18-month follow-up of the participants.Methods : Participants included parents and children who participated in the PACE program in 2013–2014, where they were randomized into intervention ( n = 76) and control ( n = 73) groups. At the 18-month follow-up, participating parents completed questionnaires on their children's learning and behavior, and their own parenting. Children were individually assessed on their preschool concepts. There were 44 intervention group and 11 control group participants with complete data.Results : The results suggested that the intervention group participants were able to maintain their program gains at 18-month follow-up in children's learning, behavior and parents' own parenting, while there were no significant differences across the three time points for the control group participants.Conclusion : The results provided some initial evidence on the sustainability of the PACE program.